A multicenter study to evaluate automated platelet aggregometry on Sysmex CS‐series coagulation analyzers—preliminary findings. Issue 4 (30th August 2018) - Platton, Sean; McCormick, Áine; Bukht, Musfira; Gurney, David; Holding, Ian; Moore, Gary W.
Abstract: Background and Objectives: Investigations of platelet function by light transmission aggregometry (LTA) using a dedicated aggregometer is time consuming and labor intensive. This multicenter study evaluated an automated LTA method using a coagulation analyzer to establish reference ranges and ideal testing regimen. Methods: Sysmex CS‐2x00 series analyzers were used to measure aggregation using a range of agonists and concentrations: ADP (1‐20 μM); arachidonic acid (0.5‐1.5 mM); collagen (1.25‐5 μg/mL); ristocetin (0.5‐1.5 g/L); epinephrine (5‐10 μM); TRAP (1‐20 μM); U46619 (1 μM); and saline. Maximum and final aggregation, disaggregation, slope, and acquisition time were compared for each. Results: For 42 normal subjects there was no significant difference in aggregation parameters for: 10 μM and 20 μm ADP; 2 and 2.5 μM ADP; 1 and 1.5 mM arachidonic acid; 2.5 and 5 μg/mL collagen; 1 and 1.25 μg/mL collagen; 1.25 and 1.5 g/L ristocetin; 5 and 10 μM epinephrine; 5 and 10 μM or 20 μM TRAP. Maximum aggregation was reached by 300 seconds with 20 and 10 μM ADP, 1 μM U46619, 1 and 1.25 μg/mL collagen, 1.5 g/L ristocetin and 5, 10, and 20 μM TRAP: all others agonists required 600s. Conclusions: A standard panel of agonists can be used on the Sysmex CS‐2x00 series analyzers: ADP (10, 5, 2.5, and 1.25 μM); 1 mM arachidonic acid; 1 μM U46619; 2.5 and 1.25 μg/mL collagen; 1.25 and 0.5 g/L ristocetin; 5 μM epinephrine; 5 and 10 μM TRAP; and saline. Aggregation should be observed for 600 seconds for all agonists except TRAP and U46619, which require 300 seconds. If further studies confirm these concentrations detect platelet disorders then Sysmex CS‐series analyzers could replace dedicated aggregometers, or perform LTA where it is currently not available.